Spontaneous late dislocation of IOL in a case of Pseudoexfoliation Syndrome - Anand Kumar Kulariya; Bipul Baishya; C S Vyas; Arvind Chauhan (Delhi Journal of Ophthalmology)
We report a case of pseudo exfoliation (PEX) syndrome with decentration of IntraOcular Lens (IOL) in right eye and dislocation in left eye. A 60 year old patient presented to us with history of sudden diminution of vision (FC at 2 meter) in left eye (LE) without any trauma or pain. On examination his left eye showed PEX on pupillary margin and over surface of iris with mild aqueous flare and aphakia. His right eye (RE) showed IOL decentration in pupillary area with glaucomatous optic atrophy. On indirect ophthalmoscopy his IOL was found to be dropped in posterior vitreous cavity in LE. The Patient gave history of both eyes cataract surgery with IOL 24 years back with good postoperative visual recovery. Treatment options available are placement of an anterior chamber IOL, scleral fixation of IOL, iris claw lens or by fibrin glue-assisted suture less fixation of IOL. As LE was only seeing eye with myopia and glaucoma, so we did not remove IOL and gave aphakic glasses. His visual status remained stable during subsequent follow up.